Digitalization of Pediatric Dentistry: A Review (Academia Journal of Medicine, 2024)
In recent years, digitization has revolutionized various  sectors, with pediatric dentistry being no exception.  This review comprehensively summarizes the impacts  and advancements of digitization in pediatric dentistry.  The utilization of digital technologies has notably  enhanced diagnostic accuracy, treatment planning,  patient engagement, and educational tools for both  dental practitioners and their young patients. Through  the integration of digital radiography, intraoral  scanning, three-dimensional printing, and  teledentistry, the field has seen improvements in  patient comfort, reduced procedure durations, and the  personalization of dental care. The review aims to  highlight the latest developments, potential  challenges, and future directions in the digital realm of  pediatric dentistry.
Keywords: Digital Dentistry; Pediatric Dentistry; Oral Health; Children